PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SQUARE TERHADAP PEMAHAMAN KONSEP MATEMATIKA PESERTA DIDIK KELAS VIII SMP NEGERI 3 PADANG - Deswita . (Departemen Matematika, 2019)
Understanding of mathematical concepts is the main ability in learning that must be mastered by students. The learning objectives of mathematics will be achieved if students are able to understand the concepts of the material provided. However, the fact that understanding the mathematical concepts of class VIII students at SMPN 3 Padang still needs to be improved. An alternative that can be used to improve understanding of concepts and activities of students in the learning process is to apply a cooperative model of think pair square type. The study was conducted to determine the effect of our ability to understand concepts and activities of students by applying the TPSq. This type of research is quasi-experimental with the design of Static Group Design. For testing the hypothesis t-test is used. Based on the results of data analysis, obtained P-value = 0.020 <α = 0.05 so it can be concluded that the ability to understand mathematical concepts of students with TPSq is better than the ability to understand mathematical concepts of students whose learning applies conventional learning to class VIII of SMPN3 Padang.Keywords— cooperative learning, Think Pair Square, mathematical concepts, conventional learning